First checklist of the chrysidid wasps (Hymenoptera: Chrysididae) of Iran - Rosa, Paolo; Lotfalizadeh, Hosseinali; Pourrafei, Leyli (Zootaxa, 2013)
A first checklist of the Iranian Chrysididae is proposed. The list includes 184 species in 20 genera. Seventy species and genera Spinolia Dahlbom, 1854, Spintharina Semenov, 1892, Trichrysis Lichtenstein, 1876 are newly recorded from Iran. New combination is proposed for Chrysura laconiae (Arens, 2001), comb. nov. (from Chrysis) and Chrysura pyrogaster turca (Linsenmaier, 1997), comb. nov. (from Chrysis). New synonymy is proposed for Chrysura barbatula (Linsenmaier, 1968) = Chrysura barbatica Bohart, 1991, syn. nov. The status of Chrysis transcaspica Mocsáry, 1889 is resurrected. Historical data with the comments of current taxonomic position and the specific validity of some species are given.